The real exchange rate as an instrument of development policy - Arslan Razmi; Martin Rapetti; Peter Skott (University of Massachusetts, Department of Economics, 2009)
Growth is endogenous in small open economies with substantial hidden or open unemployment, even under constant returns to scale. Growth promoting policies, however, have implications for the balance of trade, and two instruments are needed in order to achieve targets for both the growth rate and the balance of trade. The real exchange rate can serve as one of those instruments. Distributional conflict imposes constraints on real exchange rate policies, but in LDCs the main exchange-rate related distributional conflict may be over the sectoral distribution of profits, rather than the real wage. This paper develops a model along these lines and presents empirical support for the hypothesis that real exchange rate undervaluations are a useful instrument for the pursuit of accumulation and growth in low income countries.
Keywords: F43; O11; O41; 330; real exchange rates; underemployment; capital accumulation; investment; growth